Role of Predation and Abundance of Biological Control Agents (Ordo Hemiptera, Family Reduviidae) at Subang Palm Oil Plantation Experimen - Jojon Soesatrijo (Jurnal Syntax Transformation, 2023)
The Hemiptere Order of the Family Reduviidae has an important role in an ecosystem, namely as a natural enemy (predator) of insects, the hemiptera group itself and other arthropods. This study aims to determine the role of predation and the abundance of natural enemies in the order Hemiptera family reduviidae on oil palm plantations. This study and research was carried out in the area of a productive oil palm plantation in the village of Karapyak, Cintamekar Serangpanjang, Subang, Jawa Barat. This research is an exploratory research conducted from September 2022 to mid-December 2022. Sampling was carried out using the letter 'S' transect method with hand picking assisted by fishing nets. Identification was carried out in the laboratory of the Kampus Politeknik Kelapa Sawit Citra Widya Edukasi, Cibuntu, Cibitung, Bekasi. Data is presented in the form of tables and plot design drawings in the field, as well as sample images of sample species in the field. The abundance of species of the order Hemiptera Family Reduviidae was analyzed using the Shannon-Wiener Index and evenness was calculated according to the Pielou formula, the role of natural enemies was determined based on the behavior description and mouth type of the order Hemiptera Family Reduviidae. The results of the study obtained 37 individuals consisting of 7 genera. The diversity index (H') of the fauna of the order Hemiptera family Reduviidae on oil palm plantations of producing plants is 0.59 which is classified as in the low category. The evenness index (E') of the fauna of the order Hemiptera family Reduviidae on oil palm plantations of productive plants is 0.39 which is classified as depressed evenness.